Description of a new species and a key to species of the genus Tuberfemurus Zheng (Orthoptera: Tetrigoidea: Cladonotinae) from China - Deng, Wei-An; Lu, Xiang-Yi (Zootaxa, 2019)
Tuberfemurus torulisinotus Deng, sp. nov. is described with detailed illustrations of external morphology. Comparison between new species and other species of the genus Tuberfemurus Zheng, 1992 is compiled into a table for identification. New synonymy is proposed: Tuberfemurus laminatus Zheng, 1992 = Xiaitettix emeishanensis Deng, Zheng & Yang, 2012, syn. n. An updated key to species of the genus is given.